2018
DOI: 10.1186/s12874-018-0520-z
|View full text |Cite
|
Sign up to set email alerts
|

How is AMSTAR applied by authors – a call for better reporting

Abstract: BackgroundThe assessment of multiple systematic reviews (AMSTAR) tool is widely used for investigating the methodological quality of systematic reviews (SR). Originally, AMSTAR was developed for SRs of randomized controlled trials (RCTs). Its applicability to SRs of other study designs remains unclear. Our objectives were to: 1) analyze how AMSTAR is applied by authors and (2) analyze whether the authors pay attention to the original purpose of AMSTAR and for what it has been validated.MethodsWe searched MEDLI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 30 publications
2
50
0
1
Order By: Relevance
“…For study quality, we calculated an overall AMSTAR score and used an arbitrary cut-off (ie, 50%) to distinguish low and high quality reviews. Both approaches are discussed in the literature, since the calculation of an overall quality score assumes that all questions are of equal importance and different cutoffs exist (39,40). Both other cut-off points to define reviews of high quality as well as a three category approach (with low, moderate, and high quality) have been used to distinguish between reviews of higher or lower quality (39).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For study quality, we calculated an overall AMSTAR score and used an arbitrary cut-off (ie, 50%) to distinguish low and high quality reviews. Both approaches are discussed in the literature, since the calculation of an overall quality score assumes that all questions are of equal importance and different cutoffs exist (39,40). Both other cut-off points to define reviews of high quality as well as a three category approach (with low, moderate, and high quality) have been used to distinguish between reviews of higher or lower quality (39).…”
Section: Discussionmentioning
confidence: 99%
“…Both approaches are discussed in the literature, since the calculation of an overall quality score assumes that all questions are of equal importance and different cutoffs exist (39,40). Both other cut-off points to define reviews of high quality as well as a three category approach (with low, moderate, and high quality) have been used to distinguish between reviews of higher or lower quality (39). However, meta-reviews that applied a three category approach often merged findings from moderate and high quality studies in the same category for an evidence synthesis (16).…”
Section: Discussionmentioning
confidence: 99%
“…Participants also reported that they consider the inclusion of previous evidence synthesis to be useful for streamlining. While the use of pre-existing reviews was one strategy proposed for development of RRs, it is important to note that this strategy depends on the availability of existing SRs that satisfy the updated standards of preferred reporting items [26][27][28]. These may not exist for all topics.…”
Section: Discussionmentioning
confidence: 99%
“…Critical Appraisal Skills Programme: CASP, ). These instruments should be carefully applied and their use described in detail by meta‐review authors (Pieper, Koensgen, Breuing, Ge, & Wegewitz, ), including whether modifications were applied. Similar to the process for data extraction, meta‐review teams should engage in training of assessors and a pilot implementation period of these tools to ensure that their application is accurate.…”
Section: Steps For All Types Of Systematic Syntheses Applied To Meta‐mentioning
confidence: 99%